Assessing for mild TBI among Iraq and Afghanistan veterans: Outcomes of injury severity and neurological factors. (23rd February 2016) - Lau, Karen M.; Madden, Erin; Neylan, Thomas C.; Seal, Karen H.; Maguen, Shira
Abstract: Objective : To investigate injury severity markers and neurological symptoms associated with clinician-confirmed mild traumatic brain injury (TBI) among Iraq and Afghanistan veterans. Setting : Department of Veterans Affairs (VA) medical centre and five affiliated community-based outpatient clinics. Participants : Three hundred and fifty Iraq and Afghanistan veterans with positive initial VA TBI screens between 1 April 2007 and 1 June 2010 and clinician-confirmed TBI status by 1 December 2010. Methods : Retrospective-cohort study of medical record data. Main measures included clinician-confirmed TBI status, injury severity markers (e.g. loss of consciousness (LOC), post-traumatic amnesia (PTA) or confusion/disorientation) and neurological symptoms. Results : Among veterans who screened positive on the initial VA TBI and then received a clinician evaluation, 60% were confirmed to have a TBI diagnosis. Veterans reporting at least one LOC, confusion or PTA were almost 18-times more likely to receive a confirmed TBI diagnosis. Odds of clinician-confirmed TBI were 2.5–3-times greater among those who endorsed dizziness, poor coordination, headaches, nausea, vision problems and/or irritability, compared to those not endorsing these symptoms. Nausea had greatest utility for confirming a TBI. Conclusions : Identification of neurologic symptoms that most contribute to a clinician-confirmed diagnosis of TBI has potential for streamlining detection of TBI and symptoms needed for treatment.